The Use of Valuations in Residential Property Investment in Australia - Mangioni, Vince (International Journal of Property Sciences (E-ISSN: 2229-8568), 2009)
Residential property investment for many purchasers is subject to finance. This finance is subject to two important criteria, the first criteria being the ability of the purchaser to service a loan and the second criteria and perhaps most crucial, is the relativity of the purchase price of property to its value. This paper is a critique of the use of valuations in Australia used to engineer the lending of money against property after the purchase price has been determined. This is in contrast to the use of valuations prior to the purchase of property. A survey of several professions has been undertaken in determining the importance of a valuation in the property purchase process, which includes the formulation of the price to be paid for property. In highlighting support for the use of valuations in the property purchase process prior to the purchase of residential property, this paper makes a contribution by defining the way valuers may be engaged by the borrower prior to purchase, rather than the long standing tradition of the valuer being solely engaged by the lender after the purchase price has been determined.